Plant Foraging Strategies Driven by Distinct Genetic Modules: Cross-Ecosystem Transcriptomics Approach - Sugimura, Yusaku; Kawahara, Ai; Maruyama, Hayato; Ezawa, Tatsuhiro (Frontiers in Plant Science, 2022)
Plants have evolved diverse strategies for foraging, e.g., mycorrhizas, modification of root-system architecture, and secretion of phosphatase. Despite extensive molecular/physiological studies on the individual strategies under laboratory/greenhouse conditions, there is little information about how plants orchestrate these strategies in the field. We hypothesized that individual strategies are independently driven by corresponding genetic modules in response to deficiency/unbalance in the nutrients. Roots colonized by mycorrhizal fungi, leaves, and root-zone soils were collected from 251 maize plants grown across the US Corn Belt and Japan, and the transcriptomes of the roots were subjected to gene-coexpression network analysis. Nineteen genetic modules were defined and functionally characterized, from which three genetic modules, mycorrhizal formation, phosphate-starvation response (PSR), and root development, were selected as those directly involved in foraging for analyzing environment-module interplays. Mycorrhizal module consists of the genes responsible for mycorrhizal formation and was upregulated by both phosphorus and nitrogen deficiencies. The PSR module that consists of the genes encoding phosphate transporter, secreted acid phosphatase, and enzyme involved in internal-P recycling was regulated independent of the mycorrhizal module and strongly upregulated by phosphorus deficiency relative to nitrogen. The root development module that consists of regulatory genes for root development and cellulose biogenesis was upregulated by phosphorus and nitrogen enrichment, and its expression was negatively correlated with that of the mycorrhizal module, suggesting that root development is intrinsically an opposite strategy of mycorrhiza. Our approach provides a new insight into understanding plant foraging strategies in complex environments at the molecular level.